PENGARUH PREMI MITRA MABRUR DAN INFLASI TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan AJB Bumiputera 1912 Syariah KC Tasikmalaya 2007-2014) - Mochamad Iqbal (MNJ 15 UMY 322, 2015)
*322 This study aimed to analyze the Influence of Mitra Mabrur Premium and inflation on profitability of the Company (Study at AJB Bumiputera 1912 Syariah Company Branch Offices Tasikmalaya Period 2007-2014). Factors tested in this study is Mitra Mabrur Premium , Inflation , and Profitability. The sampling technique used was purposive sampling method in AJB Bumiputera 1912 Syariah Company Branch Offices Tasikmalaya during the years, 2007, 2008, 2009, 2010, 2011, 2012, 2013, and 2014 with a total sample of 32 accumulated premiums per quarter ( 3 months ) . The analysis technique used is multiple linear regression.